Comunicado "Aos Democratas Portugueses"
"Aos Democratas Portugueses", comunicado da Oposição, assinado por Afonso Costa (filho), Alberto Ferreira, Alberto Nogueira Gonçalves, Arnaldo Veiga Pires, Artur Castilho, Artur de Oliveira Valença, Carlos Cal Brandão, Eduardo Ferreira dos Santos Silva, Eduardo de Sousa Figueiredo, Eduardo Ralha, Fernando Lopes, Florindo Eugénio Madeira, Gustavo Soromenho, Jacinto Simões, João Eurico Caldeira Tavares, José de Magalhães Godinho, Jorge Velês Caroço, Luís da Câmara Reis, Luís Dias Amado, Luís Henrique Cordeiro, Manuel Rosa Portilheiro, Mário de Azevedo Gomes, Pina de Morais, Vasco da Gama Fernandes, a propósito das próximas eleições legislativas em Novembro